Participants in groundwater markets: who are sellers? - Mi, J.; Huang, J.; Wang, S.; Mukherji, Aditi (2008)
Few studies have paid attention to the groundwater market in rural China though it has developed rapidly in recent decades. The main objectives of this paper are to describe the main characteristics of participants of rural groundwater market and identify the determinants of selling water. Data used in this research comes from 150 households in two provinces in northern China. Based on our field survey, we find that the farmers with higher wealth, more advantaged in agricultural activity, and higher social position are more likely to be the sellers. Transaction costs also have impacts on participants in the groundwater market.